2012
DOI: 10.1134/s1070427212040131
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytic nickel sulfide in a model electrochemical capacitor

Abstract: Operation of an electrode made of electrolytic nickel sulfi de in a prototype electrochemical capacitor with potassium hydroxide solutions of various concentrations was studied by cyclic voltammetry.The growing demand for power sources for modern communication facilities and transportation require that a power source should combine high stored energy with high output power. These requirements are satisfi ed by hybrid systems combining rechargeable batteries of the type of lithium-ion intercalation systems and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The voltammetric responses of NiS electrode at different scan rates are shown in figure 3. It was found that the current under curve is slowly increased with scan rate [5][6][7][8][9]. Maximum capacitance obtained for NiS at 50 mVs -1 scan rate is 353 Fgm -1 .…”
Section: Electrochemical Properties Of the Nis Thin Film Electrodementioning
confidence: 90%
See 1 more Smart Citation
“…The voltammetric responses of NiS electrode at different scan rates are shown in figure 3. It was found that the current under curve is slowly increased with scan rate [5][6][7][8][9]. Maximum capacitance obtained for NiS at 50 mVs -1 scan rate is 353 Fgm -1 .…”
Section: Electrochemical Properties Of the Nis Thin Film Electrodementioning
confidence: 90%
“…In present work, electrochemical capacitive properties of the NiS thin film electrodes were investigated for improve supercapacitor performance. Many articles related to studies of NiS electrode for capacitive performance have been appeared in the literature [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the current under curve is slowly increased with scan rate. This showed that voltammetric currents are directly proportional to the scan rate of CV, indicating an ideally capacitive behavior [14][15][16][23][24][25].…”
Section: Supercapacitive Properties Of the Nis Thin Film Electrodementioning
confidence: 93%
“…After 3000 cycles, a high specific capacitance of 778.8 Fg -1 maintains at current density is 4 Ag -1 [15]. Apostolova et al reported a thin-layer NiS electrode is capable of reversible electrochemical transformation during more than 200 cycles with an output capacitance of 143 Fg -1 [16]. Among these deposition techniques, chemical bath deposition presently attracts considerable attention, as it does not require sophisticated instrument.…”
Section: Introductionmentioning
confidence: 99%
“…It can be synthesized in various nanostructured morphologies with great ease and it nds applications in both electrochemical energy storage devices and photovoltaic cells. [30][31][32][33][34][35][36] However, the synthesis of nickel sulde with uniform nanostructured shapes and in pure phase is an arduous task. 37 Some interesting results are summarized here.…”
Section: Introductionmentioning
confidence: 99%